Universities in India: Study of Various Types of Universities Operational in India as of 2024 From Faculty Perspective - Suresh D. Mane (International Journal of Education Sciences, 2025)
The Indian university system, a legacy of British colonial rule, has witnessed significant growth post-independence. The recent implementation of the National Education Policy (NEP) 2020 further accelerates this expansion, aiming to dismantle the affiliation system and foster the growth of autonomous colleges and universities. This study explores the forms, traits, and difficulties of Indian universities, revealing their variegated environment. It looks at how various institutions respond to the rising demand for higher education and adjust to changing educational policy. To gain insights into the perspectives of key stakeholders, the researcher conducted discussions with faculty members from various universities across India. Through a collaborative process, open-ended and closed-ended questions were formulated to construct a structured questionnaire. A random sample of faculty members was given access to this questionnaire through Google Forms, allowing information about their perspectives and experiences to be gathered. Important insights into the current situation of Indian institutions are provided by the examination of the data gathered. The results provide insight into the system's advantages, disadvantages, and prospects as well as how NEP 2020 might affect its course going forward. The study's conclusions include suggestions for improving faculty development, maximizing the operation of Indian institutions, and guaranteeing their continuous expansion and advancement in the twenty-first century. Indian higher education can become more inclusive, globally competitive, and in line with the demands of a changing knowledge economy by tackling current issues and seizing new opportunities.
Keywords: Central University; State Private University; State University; University Grants Commission; higher education